Гендерные особенности электронной коммуникации в Интернете - Горошко, Елена Игоревна (Харківський національний університет внутрішніх справ, 2005)
Исходя из теоретического предположения, что тендер является социальной конструктивистской категорией, в работе анализируются ресурсы и способы "создания" тендера на примере изучения электронного общения посредством сети Интернет в Украине.

It explores Internet and gender begginning from the assumption thet gender presents a social and cultural construct. This exploration is aimed towards understanding the ways in which Internet as very specific and not gender-neutral medium impacts and contributes to the construction of gender practices in Ukraine.
Gender aspects of electronic communication in the Internet
Keywords: коммуникативное соперничество; коммуникативное сотрудничество; чат; анонимность